Prospective, Single-Center, Six-Month Study of Intravitreal Ranibizumab for Macular Edema with Nonproliferative Diabetic Retinopathy: Effects on Microaneurysm Turnover and Non-Perfused Retinal Area - Lee SJ (Dove Medical Press, 2020)
Seung Joon Lee,1,2 In Choel Shin,1,2 Il Won Jeong,1,2 Chang Wook Choi,1,2 Yun Sik Yang1,2 1Department of Ophthalmology, Wonkwang University College of Medicine, Iksan, Korea; 2Institute of Wonkwang Medical Science, Wonkwang University, Iksan, KoreaCorrespondence: Yun Sik YangDepartment of Ophthalmology, Wonkwang University Hospital, #895 Muwang-Ro, Iksan, 54538, KoreaTel +82 63 859 1370Fax +82 63 855 1801Email ysyang@wonkwang.ac.krPurpose: To analyze the effects on microaneurysm (MA) and perifoveal perfusion in nonproliferative diabetic retinopathy (NPDR) patients with macular edema (ME) after early intensive treatment using intravitreal ranibizumab (IVR) injections.Patients and Methods: Prospectively, 25 eyes of 25 type 2 diabetes mellitus patients with ME were included between August 2016 and February 2019. For 6 months, patients were administered 0.5-mg IVR injections monthly. Ocular evaluation, including best-corrected visual acuity (BCVA; using the Early Treatment Diabetic Retinopathy Study chart), central retinal thickness (CRT; using optical coherence tomography), fundus photography, and fluorescein angiography, was performed for all participants. Results obtained at baseline were compared to those observed after 6 months.Results: Mean BCVA increased significantly from 67.6± 3.29 letters at baseline to 76.36± 1.61 letters after 6 months (P=0.002) of IVR therapy. CRT decreased significantly from 479.12± 16.66 μm at baseline to 369.12± 13.02 μm at 6 months. Similarly, the total number of MAs decreased significantly from 5.68± 3.41 to 1.60± 1.73 (P< 0.0001). MA turnover, calculated by adding the MA formation rate to the MA disappearance rate (both calculated as MA number/month) also decreased significantly from 6.88± 3.83 to 1.92± 1.75 after treatment (P< 0.0001). Perifoveal non-perfused area decreased from 2.517± 0.456 mm2 at baseline to 2.495± 0.293 mm2 at 6 months, but the results were not statistically significant (P=0.954).Conclusion: Treatment with early intensive IVR therapy in NPDR patients with ME not only improved BCVA and CRT but also decreased MA turnover. However, in the study period of 6 months, IVR therapy did not show significant improvement in perifoveal non-perfused area.Keywords: nonproliferative diabetic retinopathy, macular edema, ranibizumab, early intensive treatment, microaneurysm